The Role of Roof Truss Construction in Optimization Structure - Jasim Jarallah Fahad Al-Kaabi (Mathematical Statistician and Engineering Applications, 2022)
In order to make an efficient roof structure, it is important to take in to consideration main factors in which effect the stress, stability, and weight for overall construction. In this paper the essential factors that introduce in the design and implement the structure and examine all forces, torque and inertias in which optimize the roof truss. Usually, to improve structural optimization design efficiency for truss implementation structure factor is the weight. Reduce of weight contribute to maintain the material, in other words the structure shall use little amount and number of elements, welds joints, and external surface area, so theuseful optimizecase usedseveral approaches in many mathematics fields.